Mechanical alloying for fabrication of advanced engineering materials - El-Eskandarany, M. Sherif (Noyes Publications, 2001)
Unique in bringing about a solid-state reaction at room temperature, mechanical alloying produces powders and compounds difficult or impossible to obtain by conventional techniques. Immediate and cost-effective industry applications of the resultant advanced materials are in cutting tools and high performance aerospace products such as metal matrix armor and turbine blades. The book is a guided introduction to mechanical alloying, covering material requirements equipment, processing, and engineering properties and characteristics of the milled powders. Chapters 3 and 4 treat the fabrication of nanophase materials and nanophase composite materials. Chapter 8 provides extensive coverage of metallic glass substances. This book is ideal for materials scientists in industry and in research, design, processing, and plant engineers in the cutting tools and aerospace industries as well as senior level students in metallurgical and mechanical materials engineering. The book will especially benefit metallurgists unacquainted with ball milling fabrication.
Keywords: Mechanical alloying.; elektronické knihy; electronic books